Effect on C-V characteristics of P-N photodetector - Chaiyasoonthorn, Sawatsakorn; Srithanachai, Itsara; Sangwaranatee, Narong (My University, 2017)
This paper is aimed at investigating the way to reduce the Pt-doped effect on silicon N-Type photodetector. The influencing of Pt-doped on silicon mechanism is an important problem because the performance of semiconductor device may decrease as a result from this process. In this paper, the obtained experimental result has shown that the Roentgen radiation can be used to reduce the influence from Pt-doped process, where C-V characteristics are the parameters to study in this experiment, from which the Roentgen radiation characteristics may change because the silicon bulk absorbs radiation of about 60%. The results have indicated that the C-V characteristics are not significantly changed. This way, radiation may induce and reduce some of the defects in silicon bulk but C-V is without change. Accordingly, parameters should be investigated to explain the defects to confirm the influence of Roentgen radiation by I-V characteristics and carrier concentration.
Keywords: Absorption; P-N photodetector; Penetration; Roentgen radiation